Application of PHITS Code to Design Linear Accelerator and its Bunker - Islam, Md Mojahidul; Waliullah, H M; Rana, Md Masud; Watabe, Hiroshi; Islam, M Rafiqul (Bangladesh Journal of Medical Physics, 2025)
This study utilized the Particle and Heavy Ion Transport code System (PHITS) Monte Carlo code to develop a computer model of a Varian CLINAC (iX) linear accelerator (LINAC) operating at 6 MV and to design the shielding for its treatment bunker. The LINAC head, comprising the target, primary collimator, flattening filter, and secondary collimator, was accurately modeled based on manufacturer specifications. A water phantom was incorporated to calculate the Percentage Depth Dose (PDD) and beam profiles for a 10×10 cm² field at a Source-to-Surface Distance (SSD) of 100 cm. The success of the model was validated by visualizing particle tracks (photons, electrons, neutrons). The maximum dose was found at a depth of 1.5 cm in water for a 6 MV beam. Furthermore, a comprehensive 3D model of a radiotherapy bunker was constructed using PHITS, with shielding composed of concrete and lead. Simulations confirmed that the designed shielding effectively reduced photon and electron doses to acceptable safety limits outside the bunker. No neutron production was observed at 6 MV, as expected. This work shows how PHITS can be applied to LINAC modeling and shielding assessment under the stated assumptions. Ban. J. Med. Phys., Vol -16, Issue -1, 2025 : 1-6